PENGEMBANGAN VIDEO PEMBELAJARAN ANIMASI BERBASIS PENDEKATAN KONTEKSTUAL PADA TEMA PERISTIWA DALAM KEHIDUPAN KELAS V SD - Benata, Oci Arma; Yasir Arafat; Linda Lia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This development research aims to produce, animation learning media based on a contextual approach to the theme of events in the occultation that is valid and practical for grade V elementary school students. The method used in this research is the research and development method. The subjects in this research were grade V elementary school students, totaling 30 people. The animation learning media based on a contextual approach to the theme of events in the occultation that was developed using the ADDIE model, namely (1) analysis (analysis stage), (2) design (design stage), (3) development (development stage), (4) implementation (implementation stage), (5) evaluation (evaluation stage). Data collection was carried out using a validation questionnaire sheet. This research produced animation learning media based on a contextual approach to the theme of events in the occultation that was valid. Data analysis techniques are carried out with validity analysis using expert validation questionnaires, practicality analysis using student response questionnaires. The result of the sheets, validation questionnaires with the basis of data analysis, the average valid value is 94%. The result of the student questionnaires with an average practicality value percentage 93%.